Cyclic response of nonductile reinforced concrete frames with unreinforced masonry infills retrofitted with engineered cementitious composites - Kyriakides, Marios; Billington, Sarah L. (My University, 2014)
A new seismic retrofit technique for unreinforced masonry infills in nonductile reinforced concrete frames is presented. The objective was to develop a light and easy to apply retrofit technique for the infills that both delays shear failure at the columns of the nonductile bounding frame when subjected to an earthquake by preventing severe deterioration of the infill wall, and enhances the ductility of the system. The retrofit technique uses sprayable engineered cementitious composites (ECCs), a micromechanically designed cement-based material reinforced with short, randomly distributed polymeric fibers. Four small-scale unreinforced masonry infilled nonductile reinforced concrete frames were tested under in-plane quasi-static cyclic lateral loading. One unretrofitted wall and three different retrofit schemes were evaluated. Continuous steel reinforcement was embedded in the ECC layer and a bonding agent was applied between the masonry wall and the ECC layer. In two retrofits the impact of two different schemes using shear dowels to connect the concrete beams with the ECC retrofit were examined. The tests have demonstrated that the ECC retrofit strategy can enhance substantially the ductility of the structural system as it undergoes cyclic lateral loading.
Keywords: Concrete and masonry structures; Engineered cementitious composites; In-plane cyclic loading; Nonductile reinforced concrete frame; Retrofit; Sprayable; Unreinforced masonry wall